2023
DOI: 10.3390/ijms24021274
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Dental Resin Composite with Sr-N-Doped TiO2 and n-HA Fillers for Antibacterial and Mineralization Effects

Abstract: Dental caries, particularly secondary caries, which is the main contributor to dental repair failure, has been the subject of extensive research due to its biofilm-mediated, sugar-driven, multifactorial, and dynamic characteristics. The clinical utility of restorations is improved by cleaning bacteria nearby and remineralizing marginal crevices. In this study, a novel multifunctional dental resin composite (DRC) composed of Sr-N-co-doped titanium dioxide (Sr-N-TiO2) nanoparticles and nano-hydroxyapatite (n-HA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
(70 reference statements)
1
4
0
Order By: Relevance
“…Therefore, both composites were subjected to MSC proliferation aiming at the assessment of biocompatibility and evidence of cytotoxic effects. It is assumed that small differences in the mineral filler ratio might significantly influence the composites’ biologic behavior, in good agreement with the literature [ 40 , 41 ]. The null hypothesis states that a small difference in mineral filler has no influence on the composites’ bioactivity in vitro.…”
Section: Introductionsupporting
confidence: 84%
“…Therefore, both composites were subjected to MSC proliferation aiming at the assessment of biocompatibility and evidence of cytotoxic effects. It is assumed that small differences in the mineral filler ratio might significantly influence the composites’ biologic behavior, in good agreement with the literature [ 40 , 41 ]. The null hypothesis states that a small difference in mineral filler has no influence on the composites’ bioactivity in vitro.…”
Section: Introductionsupporting
confidence: 84%
“…The development of a dental filling containing hydroxyapatite is also clinically relevant. The current literature indicates that such materials have antibacterial properties [ 23 , 24 ] and such compounds inhibit the formation of secondary caries located under the dental filling, caused by bacterial microleakage.…”
Section: Discussionmentioning
confidence: 99%
“…Domingo et al [ 20 ] found a 30% improvement in mechanical properties after adding HAp in the form of powder. In turn, Elkassas and Arafa [ 21 ] and Priyadarsini et al [ 22 ] confirmed that the addition of HAp on the nanometric scale improved to better understand the properties of composite materials containing hydroxyapatite fillers, and studies have examined the effect of hydroxyapatite treatment on selected mechanical properties [ 23 , 24 , 25 ]. One such property is hardness, which is easy to measure and comparable with other findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous methods have been developed to inhibit or reduce the adhesion and colonization of bacterial biofilms, including physical mixing of antimicrobial agents with resin-based materials . The releasing-type antimicrobial agents, such as metal nanoparticles, fluoride, , and chlorhexidine (CHX). Or contacting-type antimicrobial agents, like quaternary ammonium compounds (QACs) , and 2-methacryloyloxyethyl phosphorylcholine (MPC). , However, releasing-type antimicrobial agents are accompanied by the complete release of the antimicrobial agent, leading to a loss of antimicrobial efficacy.…”
Section: Introductionmentioning
confidence: 99%